Dynamic Secondary Mitral Regurgitation: Current Evidence and Challenges for the Future - Onishi, Hirokazu; Izumo, Masaki; Naganuma, Toru; Nakamura, Sunao; Akashi, Yoshihiro J. (Frontiers in Cardiovascular Medicine, 2022)
Heart failure (HF) is a challenging situation in healthcare worldwide. Secondary mitral regurgitation (SMR) is a common condition in HF patients with reduced ejection fraction (HFrEF) and tends to be increasingly associated with unfavorable clinical outcomes as the severity of SMR increases. It is worth noting that SMR can deteriorate dynamically under stress. Over the past three decades, the characteristics of dynamic SMR have been studied. Dynamic SMR contributes to the reduction in exercise capacity and adverse clinical outcomes. Current guidelines refer to the indication of transcatheter edge-to-edge repair (TEER) for significant SMR based on data from the Cardiovascular Outcomes Assessment of the MitraClip Percutaneous Therapy for Heart Failure Patients with Functional Mitral Regurgitation (COAPT) trial if symptomatic despite optimal guideline-directed medical therapy (GDMT) and cardiac resynchronization therapy (CRT), but nonpharmacological treatment for dynamic SMR remains challenging. In HFrEF patients with LV dyssynchrony and dynamic SMR, CRT can improve LV dyssynchrony and subsequently attenuate SMR at rest and during exercise. Also, a recent study suggests that TEER with GDMT and CRT is more effective in symptomatic patients with HFrEF and dynamic SMR than GDMT and CRT alone. Further studies are needed to evaluate the safety and efficacy of nonpharmacological treatments for dynamic SMR. In this review, current evidence and challenges for the future of dynamic SMR are discussed.